Effects of angular guidance in shaping neuronal polarity and neurites growth direction - Chong, Swee Tong (2015)
Neurodegeneration can result from the loss of neuronal polarity, the loss of neurite directionality or even the breakdown of neuronal networks. The ability to induce polarity, directionality and network formation will be useful in the treatments of neurodegenerative diseases. Neurons naturally reside in the brain within a surrounding network of neurites. The physical interactions between each single neuron and their environment have a major role in directing a neuron’s fate. This Final Year Project will attempt to shape a neuron’s fate with angular guidance of its neurites and establishing defined networks within polydimethylsiloxane platforms. The success of such guidance will potentially contribute to emerging neurodegeneration therapies.